The Use Of Nursery Rhymes In Improving The Preschool Pupils’ Vocabulary In Bambini School - Rahmi Usman; Irmayani Irmayani; Nurfajri Ningsih (Departement of Mathematics Education, 2024)
This research aimed to know the use of nursery rhymes in improving the preschool pupils’ vocabulary at Bambini School Makassar. The researchers applied quasi-experimental method using non-equivalent control class design. The Population of this research was the preschool pupils of Bambini School Makassar, age 3, 5 – 4 years old. The samples of this research were class A and class B, which each of class consists of 30 students. This research used cluster random sampling. The researchers chosen two classes of the preschool pupils of Bambini School Makassar randomly, as the experimental class and the control class. The two classes were given treatment. The experimental class was treated by using Nursery Rhymes while the control class was taught without Nursery Rhymes. The data were collected through oral test. The result of the data analysis showed that there was significant difference between the pupils’ score who were taught by using Nursery Rhymes and without Nursery Rhymes. It was proved by the mean score of the experimental class was higher than control class in the posttest where the control group was 65.47 while the experimental group was 79.73. Moreover, the result of test of significant analysis indicated that the use of nursery rhymes significantly improved the preschool pupils’ vocabulary. Based on the result of analysis, the researchers concluded that the use of Nursery Rhymes improved the preschool pupils’ vocabulary of Bambini School Makassar. Then, to made the use of nursery rhymes was effectively done, the teacher needed to consider the pupils’ level (who), materials (what), venue (where), and time (when) the teaching and learning process taken place.